Investment attractiveness in BRICS+ economies: Evaluating business environment reforms, institutional quality, and macroeconomic factors - Mark Awe Tachega; Junjian Wang; Yanjiao Chen; Rizwan Ahmed; Erica Odwira Opoku; Clement Mintah; Leonora Bart-Plange (PLoS ONE, 2025)
Investment is a key driver of economic growth in emerging markets, yet the factors that enable or hinder foreign direct investment (FDI) and domestic investment (DI) remain contested. Regulatory reforms aimed at improving the ease of doing business (EDB) have been widely promoted as a means to attract capital, but empirical evidence on their effectiveness, especially in diverse and institutionally heterogeneous economies, is mixed. This study examines how EDB affects investment flows in nine BRICS+ economies (Brazil, Russia, India, China, South Africa, Egypt, Ethiopia, Iran, and the United Arab Emirates) over 2004–2020. Three objectives guide the analysis: assessing the direct EDB-investment link, testing the mediating role of institutional quality, specifically, regulatory quality, government effectiveness, and control of corruption, and analyzing moderation by financial development, economic freedom, and macroeconomic stability. A Pooled Mean Group, Autoregressive Distributed Lag (PMG-ARDL) approach is employed for the panel estimations, complemented by Structural Equation Modelling (SEM) to quantify mediation effects. The results reveal a dual effect of EDB, as it stimulates DI but exerts a modest negative long-term impact on FDI, likely due to transitional adjustment costs and the withdrawal of targeted investment incentives. Mediation analysis shows that institutional quality strongly channels the benefits of EDB to both FDI and DI, with indirect effects often exceeding direct ones. Financial development strengthens the positive EDB-investment relationship, while economic freedom and inflation partially dampen it. Country-specific results indicate substantial heterogeneity in the EDB-investment nexus, with some economies experiencing counterintuitive or insignificant effects. Policy implications differ by investment type. For FDI, reforms should be sequenced gradually, supported by transitional incentives, and aligned with targeted institutional strengthening to offset short-term deterrents. For DI, priority should be given to reducing operational costs, expanding access to finance, and maintaining macroeconomic stability, which collectively enhance domestic firms’ capacity to invest and grow.